Online PBPD and Coaching for Teaching SRSD Argumentative Writing in Middle School Classrooms - Amber B. Ray; Tara E. Mason; Kate E. Connor; Crystal S. Williams (MDPI AG, 2024)
Teachers report a need for professional development in order to feel more confident and be more effective in providing writing instruction and intensive intervention to support middle school students. This study investigates the impacts of online practice-based professional development (PBPD) and coaching for self-regulated strategy development (SRSD) argumentative writing instruction on teachers' implementation of the instruction. Using a pre-test-post-test design, the study also examined the effects of the SRSD instruction on students' argumentative writing from source texts. Five middle school teachers from three regions across the United States participated in the PBPD and implemented SRSD with 55 middle school students with high-incidence disabilities or below-proficient writing skills. Following PBPD, teachers implemented the SRSD argumentative writing instruction with high adherence to dosage, fidelity of implementation, and quality. Student writing was scored for argumentative genre elements, holistic quality, total words written, and transition words. Results demonstrate that students improved on all measures. In addition, students reported feeling confident in their argumentative writing abilities. Teachers and students reported high social validity for the intervention. The benefits found in this research study provide a strong foundation supporting the application of comprehensive online PBPD with follow-up coaching to support teacher implementation of SRSD.